Blood Biomarkers in Minor Stroke and Transient Ischemic Attack - Li, Jiejie (Neurosci Bull, 2016)
Minor stroke and transient ischemic attack (TIA) are common disorders with a high rate of subsequent disabling stroke, so the early recognition and management of minor stroke and TIA is of great importance. At the moment, the diagnosis of these disorders is based on neurologic deficits in a stroke-clinician’s examination of the patient, supplemented by the results of acute brain imaging. However, high variability in TIA diagnosis has been reported between physicians, even trained vascular neurologists, and image-based diagnostic confirmation is not always readily available. Some patients still have ischemic events despite sustained standard secondary preventive therapy. Blood biomarkers are promising to aid in the diagnosis, risk stratification, and individual treatment of minor stroke and TIA. Some studies are being conducted in this field. This mini-review aims to highlight potential biomarkers for diagnosis and those helpful in predicting the risk of future stroke and the selection of treatment.